2020
DOI: 10.1111/jog.14188
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after day 5 versus day 6 blastocyst‐stage embryo transfer: A systematic review and meta‐analysis

Abstract: Aim To compare the pregnancy outcomes after day 5 blastocyst‐stage embryo transfers (BET) versus day 6 BET following vitrified‐warmed cycle and to evaluate whether the number of embryos transferred and the chromosomal status of embryo influence effect estimates. Methods A literature search (PubMed, Embase and MEDLINE) up to January 2019 was conducted to identify studies where women with day 6 BET were compared to women with day 5 BET. Only studies published in English language, on peer‐reviewed journal were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…A meta-analysis from 2010 demonstrated that day 6 embryos that were at the same stage of development at cryopreservation as day 5 cryopreserved embryos, had similar clinical pregnancy and live birth rates 5 . A Recent meta-analysis found that day 5 blastocysts transfers have higher clinical pregnancy (CPR) and live birth rates (LBR) compared with day 6 embryos in both frozen and fresh cycles, regardless to embryo quality, in agreement with preceding retrospective studies 6 8 . The studies included were composed of heterogeneous patients, protocols and freezing methods.…”
Section: Introductionsupporting
confidence: 68%
“…A meta-analysis from 2010 demonstrated that day 6 embryos that were at the same stage of development at cryopreservation as day 5 cryopreserved embryos, had similar clinical pregnancy and live birth rates 5 . A Recent meta-analysis found that day 5 blastocysts transfers have higher clinical pregnancy (CPR) and live birth rates (LBR) compared with day 6 embryos in both frozen and fresh cycles, regardless to embryo quality, in agreement with preceding retrospective studies 6 8 . The studies included were composed of heterogeneous patients, protocols and freezing methods.…”
Section: Introductionsupporting
confidence: 68%
“…In fresh embryo transfer cycles, the stimulation induced endometrial advancement causes a superiority of day 5 blastocysts compared to day 6 in terms of pregnancy and implantation potential [ 39 ]. Though a recent meta-analysis indicated the benefit of day 5 blastocysts in both fresh and frozen embryo transfer cycles [ 40 ], the available low quality of clinical evidence still questions the superiority of day 5 blastocysts [ 41 ]. More specifically, in case of euploid frozen embryo transfer cycles, day 5 and day 6 blastocysts have shown a similar pregnancy potential [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the high-quality blastocyst rate of D6 group is significantly higher than that of the overnight group, indicating that the embryos in the early degranulation group have more potential for continued development. However, the formation rate of D6 high-quality blastocysts is lower in both groups, and the euploidy rate and transfer success rate of D5 blastocysts are higher than those of D6 blastocysts, and the blastocysts formed by D5 are paid more attention [ 29 ]. At present, it is believed that the metabolites of sperm and granulosa cells in the fertilized fluid are not conducive to embryonic development, and the fertilized fluid should be transferred as soon as possible [ 21 ].…”
Section: Discussionmentioning
confidence: 99%